(untitled) (Revista Apotheke, 2023)
The present study entitled "Comic Books in Initial Education in Visual Arts" explores the integration of comic books in the initial education process of Visual Arts teachers. The research encompasses the referentiality of contemporary artists and comic book creators, highlighting how their contributions enhance pedagogical practice. Utilizing the triangular approach as a methodology, the study focuses on image analysis, contextualization, and artistic practice. Initial education in Visual Arts serves as the core foundation, as the work aims to deepen the understanding of how comic books can be effectively integrated into teaching, providing future teachers with a versatile means to promote creative expression and critical analysis.